APPROPRIATE USE OF ORAL ANTIHYPERTENSIVE DRUGS EVALUATION IN NONDIALYSIS CHRONIC KIDNEY DISEASE PATIENT OF PRIVATE HOSPITAL IN EAST BEKASI 2018-2020 (STIKes Mitra Keluarga, 2021)
Introduction: Chronic Kidney Disease (CKD) is currently one of the most common diseases and being a concern in the world, including in Indonesia. The number of patients with CKD tends to increase year by year. Hypertension is a cause and effect of CKD and contributes to its development. This study aimed to evaluate the appropriateness use of oral antihypertensive drugs in patients with chronic kidney disease of private hospital in East Bekasi for the 2018-2020 period. Method: The method used in this study was observational data taken retrospectively from the medical records of non- dialysis chronic kidney disease patients. The study population were all patients diagnosed with non-dialysis chronic kidney disease at the inpatient installation of private hospital in East Bekasi. The sample was taken by consecutive sampling method where the sample was determined based on the inclusion criteria of 50 patients. Results: Evaluation of drug use in this study included right patient, right indication, right medication and right dose. The following results were obtained: right patient was 100%, right indication was 98%, right medication was 86% and right dose was 94.84%. Conclusion It can be concluded that evaluation of oral antihypertensive drugs usage in patients with chronic kidney disease need to be done so that the contribution of hypertension to CKD development decreases.